Sacred Violence, Mimetic Rivalry, and War - Konner, Melvin (Mimesis and science, 2011)
In brilliantly original works such as Things Hidden since the Foundation of the World (the source of the epigraph) and Violence and the Sacred , Ren Girard confronts fully a possibility that most modern social scientists have shied away from: that bloodshed may be at or close to the heart of all human social life. The above quote occurs in the context of a conversation about the theories and movements spawned by Marx, Nietzsche, Freud, and even Foucault, all of which might be characterized as enthusiasms for which Girard has limited sympathy. Although they all share his willingness to acknowledge the